TRANSVERSE LAPAROTOMY DURING COLON OPERATIONS - Ярослав Миронович Лещишин; Илья Васильевич Савостьянов; Иван Юрьевич Данильченко; Юрий Борисович Развозжаев; Игорь Григорьевич Мутагасимов (Медицина в Кузбассе, 2019)
Anatomical and physiological characteristics indicate the advantages of transverse laparotomy in comparison with the median access, but the spatial characteristics of these approaches were practically not subjected to comparative evaluation.